Biomechanical Leg Muscle Function During Stair Ambulation in Men Receiving Androgen Deprivation Therapy. (16th July 2019) - Cheung, Ada S; Gray, Hans A; Schache, Anthony G; Hoermann, Rudolf; Bicknell, Jarrod; Joon, Daryl Lim; Zajac, Jeffrey D; Pandy, Marcus G; Grossmann, Mathis
Abstract: Background: The role of testosterone in maintaining functional performance in older men remains uncertain. Methods: We conducted a 12-month prospective, observational case–control study including 34 men newly commencing androgen deprivation therapy for prostate cancer and 29 age-matched prostate cancer controls. Video-based motion capture and ground reaction force data combined with computational musculoskeletal modeling, and data were analyzed with a linear mixed model. Results: Compared with controls over 12 months, men receiving androgen deprivation therapy had a mean reduction in circulating testosterone from 14.1 nmol/L to 0.4 nmol/L, associated with reductions in peak knee extension torque, mean adjusted difference (MAD) –0.07 Nm/kg (95% confidence interval [CI]: –0.18, 0.04), p = .009, with a corresponding more marked decrease in quadriceps force MAD –0.11 × body weight (BW) [–0.27, 0.06], p = .045 (equating to a 9 kg force reduction for the mean body weight of 85 kg), and decreased maximal contribution of quadriceps to upward propulsion, MAD –0.47 m/s 2 [–0.95, 0.02], p = .009. We observed between-group differences in several other parameters, including increased gluteus maximus force in men receiving androgen deprivation therapy, MAD 0.11 × BW [0.02, 0.20], p = .043, which may be compensatory. Conclusions: Severe testosterone deprivation over 12 months is associated with selective deficits in lower-limb function evident with an important task of daily living.